ANALYSIS OF THE INNER CONFLICT OF THE MAIN CHARACTER IN THE NOVEL "GADIS PANTAI" BY PRAMOEDYA ANANTA TOER AND ITS UTILIZATION IN THE ENRICHMENT BOOK FOR 12TH GRADE HIGH SCHOOL NOVELS: (A Study of Literary Psychology) - Jannah, Dewi Raudlatul; Subaweh, Ahmad Maskur; Effendi, Irfan (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2023)
The world of literature, particularly the novel, serves as an indispensable contribution that delves into the profound aspects of the human experience. Literary psychology, as a branch of literary studies, delves into the intricate psychological facets experienced by characters within novels. In this context, Sigmund Freud's psychoanalytic theory identifies three fundamental elements of inner conflict: the Id, Ego, and Super Ego. Simultaneously, the emotional classifications elucidated by Albetrine Minderop encompass emotions such as guilt, self-punishment, shame, sadness, hatred, and love. This research endeavors to reveal and dissect the emotional classifications delineated by Albetrine Minderop. Employing qualitative descriptive research methodology, this study aims to scrutinize the conditions, circumstances, or aspects previously delineated, with the findings presented in the form of a comprehensive research report. The analysis within this study revolves around the inner conflicts experienced by the central character in Pramoedya Ananta Toer's novel, "Gadis Pantai." This research offers an intriguing perspective through the lens of literary psychology, providing a platform for new perspectives and insights.